The role of secreted osteoclastogenic factor of activated T cells in bone remodeling - Ruonan Zhang; Shuang Peng; Guangxun Zhu (Elsevier, 2022)
The process of bone remodeling is connected with the regulated balance between bone cell populations (including bone-forming osteoblasts, bone-resorbing osteoclasts, and the osteocyte). And the mechanism of bone remodeling activity is related to the major pathway, receptor activator of nuclear factor kappaB (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) signaling axis. Recently, researchers have found a novel cytokine secreted by activated T cells, which is related to osteoclastogenesis in the absence of osteoblasts or RANKL, leading to bone destruction. They name it the secreted osteoclastogenic factor of activated T cells (SOFAT). SOFAT has been proven to play an essential role in bone remodeling, like mediating the bone resorption in rheumatoid arthritis (RA) and periodontitis. In this review, we outline the latest research concerning SOFAT and discuss the characteristics, location, and regulation of SOFAT. We also summarize the clinical progress of SOFAT and assume the future therapeutic target in some diseases related to bone remodeling.